Friars and Jews in the Middle Ages and Renaissance - Myers, Susan E.; McMichael, Steven J. (Leiden ; Boston : Brill, 2004)
Historians--some specializing in the Middle Ages, some in religion, and some in a particular European country--describe the major areas scholars are working in with regard to the friars' preaching to and writing about the Jews from the early days of the mendicant order about the turn of the 13th century to the 16th century. Their topics include the.
Abbot Joachim of Fiore and the conversion of the Jews / E. Randolph Daniel -- The Antichrist and the Jews in four thirteenth-century Apocalypse commentaries / David Burr -- Archbishop Eudes Rigaud and the Jews of Normandy, 1248-1275 / William Chester Jordan -- Intimate enemies : mendicant-Jewish interaction in thirteenth-century mediterranean Spain / Larry J. Simon -- Jews and Judaism in Peter Auriol's Sentences commentary / Nancy L. Turner -- Franciscan economics and Jews in the Middle Ages : from a theological to an economic lexicon / Giacomo Todeschini -- Contempt for friars and contempt for Jews in late medieval Germany / Christopher Ocker -- The evolution of Francesc Eiximenis's attitudes toward Judaism / David J. Viera -- Samuel of Granada and the Dominican inquisitor : Jewish magic and Jewish heresy in post-1391 Valencia / Mark D. Meyerson -- Leonard Dati's sermon on the circumcision of Jeus (1417) / Thomas M. Izbicki -- Alfonso de Espina on the Mosaic law / Steven J. McMichael -- Anti-Jewish preaching in the fifteenth century and images of preachers in Italian renaissance art / Roberto Rusconi -- Franciscans, and the first Monti de pietà in Italy (1462-1500) / Ariel Toaff -- Papal mendicants or mendicant popes : continuity and change in papal policies toward the Jews at the end of the fifteenth century / Kenneth R. Stow -- The friars and the Jews : messianism in Spain and Italy circa 1500 / John Edwards -- Limpieza versus mission : church, religious orders, and conversion in the sixteenth century / Anna Foa.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Antisemitism -- Europe, Western -- History -- To 1500 -- Congresses; Jews -- Europe, Western -- History -- To 1500 -- Congresses; Friars -- Europe, Western -- History -- To 1500 -- Congresses; Christianity and antisemitism -- Europe, Western -- History -- Congresses; Europe, Western -- Ethnic relations -- Congresses; Antisemitism -- Europe -- History -- To 1500 -- Congresses; Jews -- Europe -- History -- To 1500 -- Congresses; Friars -- Europe -- History -- To 1500 -- Congresses; Christianity and antisemitism -- Europe -- History -- Congresses; Europe -- Ethnic relations -- Congresses; Antisémitisme -- Europe -- Histoire -- 500-1500 (Moyen Âge) -- Congrès.; Juifs -- Europe -- Histoire -- 500-1500 (Moyen Âge) -- Congrès.; Ordres mendiants -- Europe -- Histoire -- 500-1500 (Moyen Âge) -- Congrès.; Christianisme et antisémitisme -- Europe -- Histoire -- Congrès.; Europe -- Relations interethniques -- Congrès.; Juifs -- Europe de l'Ouest -- Histoire -- Jusqu'à 1500 -- Congrès.; Christianisme et antisémitisme -- Europe de l'Ouest -- Histoire -- Congrès.; Europe de l'Ouest -- Relations interethniques -- Congrès.; RELIGION -- Christianity -- General; RELIGION -- Christian Life -- Social Issues; Antisemitism; Christianity and antisemitism; Ethnic relations; Friars; Jews; Europe; Western Europe; Judentum; Mönchtum; Antisemitismus; Joden; Religieuze orden; Christendom; Juden; Saint Louis <Mo., 1997>; To 1500; Teologi -- Teologi; proceedings (reports); Conference papers and proceedings; History; Conference papers and proceedings; Actes de congrès.